Menopause symptom management in women with dyslipidemias: An EMAS clinical guide. (May 2020) - Anagnostis, Panagiotis; Bitzer, Johannes; Cano, Antonio; Ceausu, Iuliana; Chedraui, Peter; Durmusoglu, Fatih; Erkkola, Risto; Goulis, Dimitrios G.; Hirschberg, Angelica Lindén; Kiesel, Ludwig; Lopes, Patrice; Pines, Amos; et al.
Highlights: Systemic estrogens induce a dose-dependent reduction in TC, LDL-C and Lp(a), as well as an increase in HDL-C concentrations. Transdermal rather than oral estrogens should be used in women with hypertriglyceridemia. With regard to progestogens, micronized progesterone or dydrogesterone is preferred, due to their neutral effect on lipid profile. Menopausal hormone therapy is not recommended for the sole purpose of lipid profile improvement or cardiovascular disease risk reduction. Dietary changes and pharmacological management should be tailored to the type of dyslipidemia (statins constitute the mainstay of treatment). Abstract: Introduction: Dyslipidemias are common and increase the risk of cardiovascular disease. The menopause transition is associated with an atherogenic lipid profile, with an increase in the concentrations of total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C), triglycerides (TG), apolipoprotein B (apoB) and potentially lipoprotein (a) [Lp(a)], and a decrease in the concentration of high-density lipoprotein cholesterol (HDL-C). Aim: The aim of this clinical guide is to provide an evidence-based approach to management of menopausal symptoms and dyslipidemia in postmenopausal women. The guide evaluates the effects on the lipid profile both of menopausal hormone therapy and of non-estrogen-based treatments for menopausal symptoms. Materials and methods: Literature review and consensus of expert opinion. Summary recommendations: Initial management depends on whether the dyslipidemia is primary or secondary. An assessment of the 10-year risk of fatal cardiovascular disease, based on the Systematic Coronary Risk Estimation (SCORE) system, should be used to set the optimal LDL-C target. Dietary changes and pharmacological management of dyslipidemias should be tailored to the type of dyslipidemia, with statins constituting the mainstay of treatment. With regard to menopausal hormone therapy, systemic estrogens induce a dose-dependent reduction in TC, LDL-C and Lp(a), as well as an increase in HDL-C concentrations; these effects are more prominent with oral administration. Transdermal rather than oral estrogens should be used in women with hypertriglyceridemia. Micronized progesterone or dydrogesterone are the preferred progestogens due to their neutral effect on the lipid profile. Tibolone may decrease TC, LDL-C, TG and Lp(a), but also HDL-C concentrations. Low-dose vaginal estrogen and ospemifene exert a favorable effect on the lipid profile, but data are scant regarding dehydroepiandrosterone (DHEA). Non-estrogen-based therapies, such as fluoxetine and citalopram, exert a more favorable effect on the lipid profile than do sertraline, paroxetine and venlafaxine. Non-oral testosterone, used for the treatment of hypoactive sexual desire disorder/dysfunction, has little or no effect on the lipid profile.